Modernisasi Warisan : Sebuah Pendekatan Penciptaan Nilai Bersama untuk Inovasi Produk dan Daya Tahan Merek pada Usaha Kuliner Tradisional - Deddy Ray Girsang (Lembaga Pengembangan Kinerja Dosen, 2025)
Culinary businesses that rely on cultural heritage are faced with a core challenge: aligning the need for innovation to remain competitive with the need to maintain the authenticity that is the essence of the brand. This study investigates the potential application of the concept of value co-creation as a strategic model to address the conflict between innovation and authenticity. Using a comparative qualitative case study method on four culinary MSMEs in Medan, Indonesia, this research found that authenticity can act as a